A Randomized Control Trial of 3 IU IV Oxytocin Bolus with 7 IU Oxytocin Infusion versus 10 IU Oxytocin Infusion During Cesarean Section for Prevention of Postpartum Hemorrhage - Yaliwal RG; Biradar AM; Dharmarao PS; Kori SS; Mudanur SR; Patil NG; Shiragur SS; Mathapati SS (Dove Medical Press, 2020)
Rajasri G Yaliwal,1 Aruna M Biradar,1 Prathibha S Dharmarao,2 Shreedevi S Kori,1 Subhashchandra R Mudanur,1 Neelamma G Patil,1 Shobha S Shiragur,1 Sangamesh S Mathapati1 1Department of OBGYN, BLDE (DU) Shri B. M. Patil Medical College Hospital and Research Center, Vijayapura, Karnataka, India; 2Department of Anesthesiology, BLDE (DU) Shri B. M. Patil Medical College Hospital and Research Center, Vijayapura, Karnataka, IndiaCorrespondence: Aruna M Biradar; Rajasri G YaliwalDepartment of OBGYN, BLDE (DU) Shri B.M. Patil Medical College, Hospital and Research Center, Vijayapura, Karnataka, IndiaTel +91 81971 91472; +91 98451 52240Fax +91 8352 263303Email aruna.biradar@bldedu.ac.in; ryaliwal@bldedu.ac.inPurpose: Oxytocin is the preferred choice for prophylaxis and treatment of postpartum hemorrhage. Intravenous infusion has been a widely accepted route for Oxytocin administration. However, intravenous bolus route is not a readily preferred route due to apprehensions regarding hypotension that it may cause. This trial compares low dose 3 IU intravenous (IV) bolus Oxytocin along with 7 IU Oxytocin in intravenous infusion to 10IU Oxytocin intravenous infusion during cesarean section.Patients and Methods: A total of 250 term pregnant women were randomized to either 3 IU intravenous bolus with 7 IU intravenous infusion of Oxytocin or 10IU of intravenous Oxytocin infusion. The difference in pre- and post-operative hemoglobin levels, tone of the uterus, hemodynamic changes, adverse effects of the drug, need for additional uterotonics and need for blood transfusions were assessed.Results: There was 6.7% less blood loss in the 3 IU IV bolus Oxytocin with 7 IU Oxytocin infusion group in comparison to the Oxytocin infusion group. The tone of the uterus was firmer in IV bolus Oxytocin with Oxytocin infusion group at 5 minutes (p< 0.001) than the Oxytocin infusion group. There was no significant difference in the hemodynamic changes, adverse effects or need for blood transfusions.Conclusion: Intravenous bolus of 3 IU Oxytocin along with 7 IU infusion of Oxytocin is as safe and more effective than intravenous infusion of 10 IU of Oxytocin during cesarean section in the prevention of postpartum hemorrhage.Keywords: Oxytocin, cesarean section, blood loss, hemoglobin, uterine tone